Proposta de leitura intertextual do conto “Os três porquinhos” no Ensino Fundamental I - Massuia, Ana Paula Fernandes (2023)
This master’s thesis reports research that aimed to develop a didactic proposal for intertextual reading based on the short story “The Three Little Pigs”, aimed at students of the third year of Elementary School I. We take as an assumption the understanding that the development of reading is an essential activity in students' literacy and a practice that will accompany them throughout their lives, as it is a social practice highly present in literate societies. We also consider the assumption that the texts we come into contact with in our daily lives were not produced in isolation, but based on others previously produced, in an intertextual relationship. These assumptions guided the theoretical foundation of this master’s thesis, whose discussions and reflections are based on authors such as Geraldi (1997), Bakhtin (2003), Kleiman (2004), Koch and Elias (2007), among others, on the concept of text adopted in this study and on the importance of texts as an object of study and reading and its multiple aspects in the meaning construction; Kristeva (1974), Koch, Bentes and Cavalcanti (2008), and Koch (2014), on intertextuality; Solé (1998), on the reading strategies and reading stages; and the Base Nacional Comum Curricular (National Curricular Common Base) (Brasil, 2018), on the text as a teaching unit, among other discussions related to the teaching of the Portuguese language. We follow the interpretative qualitative approach, as it allows us to understand and interpret social phenomena inserted in a context (Bortoni-Ricardo, 2008), and it is of a propositional nature, which has as its starting point the reality of a third-year class of Elementary School I at a public school in the education system of Cascavel (Paraná, Brazil). In order to achieve the general aim, we present a didactic proposal aimed at the target auditory, which enables the students to have an intertextual reading experience of various versions of the traditional children’s story “The three little pigs” and texts of the genres cartoon and comic strip. We expect that this research can contribute to the teaching of Portuguese in the early years of Elementary School, to help develop students’ reading competence, so that they are able to understand what has been read and relate the text with other texts previously read.